Implementasi Manajemen Kelas Di Sekolah Dasar Negeri Kecamatan Bacukiki Kota Parepare - Rasmi Djabba (Publikasi Pendidikan, 2017)
This research is descriptive quantitative research to the implementation of the management class at a public elementary school districts Bacukiki Parepare. The purpose of this study was to obtain an overview of the implementation of the management class held by the teacher to the student and determine the factors that become an obstacle in the implementation of classroom management in Bacukiki Elementary School District of City of Parepare. The result showed that the ability of classroom management sub-district public primary school teachers Bacukiki Parepare in the middle category. Overall, teachers who have a grade-level management capabilities over many frequencies teachers who is in the category of moderate to very high category is the category with the very low to low category. The constraints experienced in the classroom management is lack of availability of adequate learning facilities such as completeness of the tools of learning science, social studies, and still lack of supporting books and reference in the library that can not optimize acceleration school purposes, the number of students is too much on almost in every classroom, and other barriers is very limited available of funds.Keyword: implementation of classroom management